A Tetracoordinated Phosphasalen Nickel(III) Complex1. Issue 5 (16th December 2013) - Cao, Thi‐Phuong‐Anh; Nocton, Grégory; Ricard, Louis; Le Goff, Xavier F.; Auffrant, Audrey
Abstract The oxidation of a NiII complex bearing a tetradentate phosphasalen ligand, which differs from salen by the presence of an iminophosphorane (PN) in place of an imine unit, was easily achieved by addition of a silver salt. The site of this oxidation was investigated with a combination of techniques (NMR, EPR, UV/Vis spectroscopy, X‐ray diffraction, magnetic measurements) as well as DFT calculations. All data are in agreement with a high‐valent NiIII center concentrating the spin density. This markedly differs from precedents in the salen series for which oxidation on the metal was only observed at low temperature or in the presence of additional ligands or anions. Therefore, thanks to the good electron‐donating properties of the phosphasalen ligand, [Ni(Psalen)]+ represents a rare example of a tetracoordinated high‐valent nickel complex in presence of a phenoxide ligand.